THE IMPACT OF THE MARGINALIZATION OF THE PRIVATE SECTOR IN IRAQ ON SOME ECONOMIC VARIABLES FOR THE PERIOD (2004-2018) - Inst. Dr. Bushra Ali Wahaib (Scholar Express Journals, 2023)
The private sector constitutes a fundamental axis in the economies of both advanced and developing worlds, given its capabilities that qualify it to play a pioneering role in all economic and social fields. Hence, it is essential to assign it more roles. The importance of the private sector in Iraq lies in the fact that the Iraqi economy still exhibits rentier characteristics, relying heavily on oil revenues due to the inefficiency of the overall sectors of the national economy. This necessitates reducing reliance on a single income source and moving towards diversification by restructuring the economy at both the macro and sectoral levels to ensure flexibility in facing successive changes internationally. This can be achieved by increasing the role of the private sector, expanding its contribution to the national economy, and developing its mechanisms, creating a conducive environment through activating national development plans. Thus, addressing the significant problems hindering its development.
Keywords: Corporate governance; earning management; COVID-19 pandemic